2018
DOI: 10.1021/acsenergylett.8b00835
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Silver Doping and Surface Passivation of CsPbI3 Perovskite Active Layer Enable Light-Emitting Devices with an External Quantum Efficiency of 11.2%

Abstract: Lead halide perovskite nanocrystals are currently under intense investigation as components of solution-processed light-emitting devices (LEDs). We demonstrate LEDs based on Ag doped–passivated CsPbI3 perovskite nanocrystals with external quantum efficiency of 11.2% and an improved stability. Ag and trilayer MoO3/Au/MoO3 structure were used as cathode and anode, respectively, which reduce the electron injection barrier and ensure the high transparency and low resistance of the anode. Silver ions diffuse into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
190
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 222 publications
(195 citation statements)
references
References 42 publications
3
190
2
Order By: Relevance
“…CsPbX 3 nanocrystals have been incorporated into solar cells achieving a record 13.4 % power conversion efficiency (PCE). [15] Other syntheses have expanded this general idea by generating multiple nanocrystal morphologies through ligand mediation [21][22] and reaction tuning, [23] by using different surface ligands for improved quantum yields, [24][25] by increasing surface passivation/repair via salt solutions, [26][27][28][29] as well as by generating other cation/anion compositions through doping [17,[30][31][32][33][34][35] or post-synthetic ion exchange. [12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CsPbX 3 nanocrystals have been incorporated into solar cells achieving a record 13.4 % power conversion efficiency (PCE). [15] Other syntheses have expanded this general idea by generating multiple nanocrystal morphologies through ligand mediation [21][22] and reaction tuning, [23] by using different surface ligands for improved quantum yields, [24][25] by increasing surface passivation/repair via salt solutions, [26][27][28][29] as well as by generating other cation/anion compositions through doping [17,[30][31][32][33][34][35] or post-synthetic ion exchange. [12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…[59] Importantly, the δ phase for CsPbI 3 is nonluminescent, rendering the material unusable for most applications. [17,65] A recent report by Liao et al describes the thermal stability of cesium lead halide perovskites from À 190 to 500°C using Raman spectroscopy and XRD. [52] Liu and coworkers compare CsPbI 3 nanocrystals stabilized with trioctylphosphine (TOP) to those stabilized with oleic acid and oleylamine.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In fact, many reports have validated the facile doping in lead halide perovskites due to their non-rigid structures. For example, Ag + , K + , Rb + , Sn 4+ , Sn 2+ , Zn 2+ , Cd 2+ , Bi 3+ and Mn 2+ have been applied as dopants, 1926 but none of them can enable near-infrared (NIR) emissions.…”
Section: Introductionmentioning
confidence: 99%
“…), B site doping (with Mn 2+ , Ni 2+ , Sn 4+ , Ln 3+ , etc. ), surface engineering, matrix encapsulation, and postprocessing …”
Section: Discussionmentioning
confidence: 99%
“…), 256 B site doping (with Mn 2+ , Ni 2+ , Sn 4+ , Ln 3+ , etc. ), [257][258][259][260][261][262][263][264] surface engineering, 195,197 matrix encapsulation, 196,265 and postprocessing. 161,266,267 Coupled with lattice incompleteness, many defects are presented in these NCs, including Schottky defects (cation and anion vacancies), Frenkel defects (interstitial sites), inversion defects, and structural defects (grain boundary, interface, and lattice distortion caused by impurities).…”
Section: Discussionmentioning
confidence: 99%